Black lamb and grey falcon Volume 1 A Journey through Yugoslavia - West, Rebecca (New York Viking Press, 1966)
This work is the record of a pilgrimage made at the end of the 1930s by the author and her husband throught the country of the Serbs, Croats, and Slovenes.
Vol. 1. Prologue -- Journey -- Croatia -- Dalmatia -- Expedition -- Herzegovina -- Bosnia -- Serbia
Keywords: Description and travel -- Yugoslavia; History -- Serbia; History -- Yugoslavia